The State Debate
VII, 270 p.
Keywords: The 1990s promise to be a period of rapid political change, as old political boundaries dissolve and new political forces emerge. These changes throw into question our understanding of capitalism and socialism, of the character of the nation state, and of the relationship between the economy and the state. However, these changes are only the culmination of developments which have been unfolding over the past two decades. This book includes a comprehensive introductory survey, which sets the contributions collected here within the context of the wider debate.